2010
DOI: 10.1002/acr.20326
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the natural history of forefoot bursae using ultrasonography in patients with rheumatoid arthritis: A twelve‐month investigation

Abstract: The findings of this study suggest that forefoot bursae may regress or hypertrophy over time in patients with RA, and that these changes may be associated with self-reported foot impairment and activity restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
(41 reference statements)
1
30
1
1
Order By: Relevance
“…They also demonstrated that US was superior to clinical examination which identified foot bursitis only in 23.5% of patients [44]. Same authors in 2010 [46] assessed foot of RA patients at baseline and after 12 months in order to detect forefoot bursae and determine their natural history and clinical significance. US detectable foot bursae were found in 93.3% of participants at 12 months, this result was substantially stable respect to US findings at baseline.…”
Section: C) Bursitismentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that US was superior to clinical examination which identified foot bursitis only in 23.5% of patients [44]. Same authors in 2010 [46] assessed foot of RA patients at baseline and after 12 months in order to detect forefoot bursae and determine their natural history and clinical significance. US detectable foot bursae were found in 93.3% of participants at 12 months, this result was substantially stable respect to US findings at baseline.…”
Section: C) Bursitismentioning
confidence: 99%
“…Indeed 45% of patients presented a regression of one or more bursae, while a similar number had new episodes of foot bursitis identified by US. Foot bursitis can therefore be considered a dynamic process and its identification by US is very important to better focus on treatment, as steroid injection, and preventative foot health [46].…”
Section: C) Bursitismentioning
confidence: 99%
“…Emerging evidence suggests that the use of US provides clinicians with the diagnostic capabilities to detect, grade and monitor active RA foot disease to expedite timely interventions [39,41,47,55]. Unfortunately, while US imaging has contributed towards developing understanding of inflammatory and mechanical processes in RA foot disease, little evidence exists related to the use of US in determining response to nonpharmacological interventions, such as foot orthoses and footwear modifications.…”
Section: Us Use In Assessing Efficacy Of Interventions For Ra Foot DImentioning
confidence: 99%
“…Plantar forefoot bursitis (anatomical intermetatarsal and adventitial plantar fat pad bursitis) related to RA has also recently received more attention [41,47]. Other common causes of symptoms in this area in adults that may not be directly attributable to the manifestations of RA within the foot, include Morton's neuroma, metatarsal stress fracture or predislocation syndrome (with associated capsulitis and disruption of the plantar plate) of the MTP joints [48][49][50].…”
Section: Current Evidence For Use Of Us To Detect Foot Pathology In Ramentioning
confidence: 99%
See 1 more Smart Citation